Validation of low velocity impact on a biocomposite flat plate laminates - Mohd Jamal, Qistina (2016)
Impact analysis under low velocity was carried out on flat plate structure at normal and oblique impact with energy level of 3J to 9J with interval of 3J. Utilization of natural fiber reinforced with polymer and hybridizing it with synthetic fiber were introduced. The aim of the study was to assess the effects of low velocity impact on biocomposite structure composed of chopped strand mat (CSM) glass fiber, kenaf fiber and hybrid of both materials and epoxy as resin material. Drop weight impact test of flat plate structure and determination of mechanical characterization were carried out with samples prepared under vacuum infusion method for glass/epoxy, kenaf/epoxy and hybrid composites composed of those two material. Glass/epoxy composites exhibit better mechanical properties as compared to kenaf/epoxy composites. From the experimental work, it was found that the impact energy level influenced the impact peak force proportionately. Hybrid composites generates damage propagation with combination of damage propagation from individual fiber of glass and kenaf reinforced polymer. The severity of damage was high at higher impact energy although significant damage at impact energy of 3J was detected under drop weight impact test where internal damage on all three configurations had occurred which further suggested reduction in residual strength. Finite element analysis was then carried out for flat plate model of all three configurations and validated against the experimental work. It was found that validation on all configurations meet the agreement with experimental results. Further finite element analysis considered all configuration based on the validation results for flat plate on oblique impact. The influence of impact angle was found to affect the maximum impact force of the impacted material where at higher impact energy the respond of maximum impact force was significant. However, there is slightly impact damage detected at lower impact energies under oblique impact.